Role of the Social Support and Health Status in Living Arrangement Preference of the Elderly in China—A Cross-Sectional Study - Cui, Longyan; Li, Jingshan; Xie, Danni; Wang, Minghui; He, Fanrong; Chen, Junfeng; Ding, Ding (Frontiers in Public Health, 2022)
Background Living arrangement of the elderly is one of the most important components that affect their quality of life in later years. The aging, with the phenomenon of low fertility rate and family structure transformation, has caused changes in the living arrangements of the elderly. This research aimed to find the elderly's living arrangement preferences and influencing factors. Methods The data were obtained from The Chinese Longitudinal Healthy Longevity Survey (CLHLS) in the 2018, and the sample was comprised of 9,638 individuals aged ≥ 60 years. Independent variables were divided into social support, health status and so-economic status. Chi-square test and binary logistic regression were used to analyze the relationship between the above variates and living arrangement preferences. Results Currently, in terms of living arrangement preferences, nearly half (45.6%) of the respondents choose not to live with their children. The binary model results showed that elderly who were married (OR = 0.166, 95% CI: 0.147–0.187), experienced more than 6 years of education (OR = 0.600, 95% CI: 0.517–0.695), ability of daily living (ADL) impaired (OR = 0.810, 95% CI: 0.720–0.912), suffering from multiple chronic diseases (OR = 0.803, 95% CI: 0.720–0.912), and obtained community services (OR = 0.884, 95% CI: 0.803–0.972) incline to not live with their children. The elderly who living in rural areas (OR = 1.244, 95% CI: 1.129–1.371), with an income of more than 500,000 yuan per year (OR = 1.557, 95% CI: 1.380–1.757), having children visiting regularly (OR = 1.405, 95% CI: 1.161–1.707) and receiving children's financial support (OR = 1.194, 95% CI: 1.080–1.319) are more likely to choose to live with their children. Conclusions This study found that the living arrangement preferences of the elderly were affected by social support and health status, and living with children is no longer the only option for the elderly these days. The elderly care services provided by communities or professional care institutions may become the mainstream of taking care of the elderly citizens in the aging society. Improving the types and forms of community nursing services to increase the accessibility of these services; setting up elderly care institutions reasonably and equipping adequate professional nursing staff should be considered as priority measures.